2004
DOI: 10.1016/j.electacta.2004.01.089
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial behavior of polymer electrolytes

Abstract: Abstract.Evidence is presented concerning the effect of surfaces on the segmental motion of PEO-based polymer electrolytes in lithium batteries. For dry systems with no moisture the effect of surfaces of nano-particle fillers is to inhibit the segmental motion and to reduce the lithium ion transport. These effects also occur at the surfaces in composite electrodes that contain considerable quantities of carbon black nano-particles for electronic connection. The problem of reduced polymer mobility is compounded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…This can be assigned to complexation caused by interaction among components and therefore referred to as composite of NCPE system. Kerr et al [21] have reported that when the fillers are of nanodimension and the concentration of filler particles is optimum, a composite or second may be observed in dynamic mechanical behaviour at higher temperatures. The composite is attributed to relaxation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be assigned to complexation caused by interaction among components and therefore referred to as composite of NCPE system. Kerr et al [21] have reported that when the fillers are of nanodimension and the concentration of filler particles is optimum, a composite or second may be observed in dynamic mechanical behaviour at higher temperatures. The composite is attributed to relaxation.…”
Section: Resultsmentioning
confidence: 99%
“…Thus conductivity drops significantly. At intermediate concentrations the decrease in conductivity may be due to pairing effect/re-association of free ions [1,5,21]. The second conductivity maxima is related to formation of highly conducting interfacial layer between MWNT and gel electrolyte caused by filler salt interaction which dominates over ion pairing effect [6,11,14,24].…”
Section: Xrd Studiesmentioning
confidence: 99%
“…Further support for this model was given in [6], where faster processes correspond to bulk polymer whereas slower processes are interpreted in terms of tightly bound polymer chains, whose segmental dynamics are slowed down wrt bulk dynamics as a consequence of the interaction with the silica nanoparticle surface. Further support is offered in [13], where Dynamic Mechanical Thermal Analysis suggests that polymer chain motion in polymer electrolytes is affected by the presence of nanoparticle surfaces, ie glass transition temperature increases by increasing the percentage of nanoparticles.…”
Section: Model Of Tsagaropoulosmentioning
confidence: 99%
“…This implies the possible existence of pinning/depinning transitions related to the dynamics of the interface. 7 This type of phenomenon, among others, has been observed in the crystallization of proteins, mass transfer processes in natural and synthetic porous media [8][9][10][11][12][13][14] and polymer electrolytes, [8][9] paper wetting experiments, 15 propagation of the burning front, 16 growth of bacterial colonies, 17,18 rupture of lines in paper sheets, 19 solid growth fronts, 20 electrochemical formation of solid phases, 21 tumoral growth mechanisms, 22 and their growth and spreading. [23][24][25] The diversity of processes involved in the above phenomena suggests the possibility to investigate time-dependent pinning effects that may occur, for instance, for front propagation in colloidal media.…”
Section: Introductionmentioning
confidence: 99%